Empathy among health science undergraduates toward the diagnosis of chronic pain: An experimental study. - López-Martínez, Alicia Eva; Serrano-Ibáñez, Elena Rocío; Solís-Serrano, Laura; Ramírez-Maestre, María del Carmen; Esteve-Zarazaga, Rosa (My University, 2023)
Objectives: To analyse the empathetic response of future health professionals toward people diagnosed with chronic pain differentiated by the degree of visibility and credibility of symptoms. Methods: A total of 203 undergraduates performed an experimental task using vignettes depicting different diagnoses of chronic pain and completed questionnaires measuring dispositional and situational empathy. A MANCOVA analysis was conducted. Results: The main effects of chronic pain diagnoses did not significantly affect situational empathy (p = .587, η2 = 0.007, d = 0.229). The dispositional empathy variables perspective-taking and personal distress affected the situational empathy scores (p = .002, η2 = 0.072, d = 0.906, and p = .043, η2 = 0.032, d = 0.547, respectively). Conclusions: It would seem appropriate to foster intra-individual empathy factors among health science undergraduates such that they can more readily understand the process of individual adaptation to chronic pain and thus manage it more effectively. Practice implications: It would be useful for dispositional empathy to form part of the transversal competences of the training programmes of future health professionals from the beginning of their studies.
Keywords: Dolor; Estudiantes universitarios; Chronic pain